2019
DOI: 10.1002/jnm.2599
|View full text |Cite
|
Sign up to set email alerts
|

A novel method to dynamic thermal impedance and channel temperature extraction of GaN HEMTs

Abstract: An improved method to extract dynamic thermal impedance for power transistor is proposed, and the nonlinear thermal effect is considered. A novel model to characterize transistor dynamic thermal impedance is established. A four-node R-L network is attached in model to characterize self-heating. And the method to extract model parameters is given. A constant m is defined to judge the change of thermal impedance with temperature. Thermal impedance Z th can be solved through rigorous mathematical calculation. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Gallium nitride (GaN) is characterized by high mobility, a very high electric breakdown field and high thermal conductivity which is a great advantage compared to other types of transistor [1,2]. Thanks to these and other characteristics, these transistors are used in several highfrequency and high-temperature applications [3,4], such as, telecommunication, electronic warfare (military field) and airborne systems [5,6], etc. HEMT has also been used in several systems such as high power amplifiers, radars and satellites, it is also found in radio frequency sensors and devices [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gallium nitride (GaN) is characterized by high mobility, a very high electric breakdown field and high thermal conductivity which is a great advantage compared to other types of transistor [1,2]. Thanks to these and other characteristics, these transistors are used in several highfrequency and high-temperature applications [3,4], such as, telecommunication, electronic warfare (military field) and airborne systems [5,6], etc. HEMT has also been used in several systems such as high power amplifiers, radars and satellites, it is also found in radio frequency sensors and devices [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the operating conditions influence the mechanical behaviour of the HEMT structure, these conditions generate displacements, strains and stresses in the structure [13,14]. These electro-thermomechanical phenomena give rise to degradations such as burying the gate, damaging the connection between the chip and the package [4], degradation of electron mobility and current reduction [15]. In the case of airborne systems, the majority of failures are caused by high-power amplifiers at its highpower transistors.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the characteristic of high‐power density, GaN high‐electron‐mobility transistors (HEMTs) are very attractive for high‐power applications in microwave and millimeter‐wave devices 1–5 . As the rapid development of GaN HEMT technology process, the large‐signal modeling lags behind due to its complex parameter extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Useful improvements made for HBTs are reported on the analysis of intrinsic base resistances by Chen et al, on large‐signal models by Hu et al, on the determination of cutoff and maximum oscillation frequencies by Zhang and Gao, and on the thermal resistance calculation by Wang et al Due to a high breakthrough voltage and saturation velocity, GaN HEMTs is very promising for millimeter‐wave solid‐state power amplifiers. Chen et al reported an improved quasi‐physics zone division large‐signal model to account for electro‐thermal effects, which is valid for the ambient temperature range of 245 to 390 K. Physical parameters' effects, reliable parameter extraction, and dynamic thermal impedance extraction for the equivalent circuit models of GaN HEMTs are discussed by Mi et al, Chen et al, and Wang et al, respectively. The modeling of emerging devices is also presented by Chen et al for GaN‐on‐diamond HEMTs and Zhang et al for AlGaN/GaN fin‐shaped HEMTs, which may be interesting for next generation devices.…”
mentioning
confidence: 99%